ANALYSIS OF ACCEPTANCE OF E-HEALTH APPLICATION BY USERS IN PRIMARY HEALTHCARE CENTER IN SURABAYA CITY - Ni Made Mira Wahyu Astani; Ni Luh Putu Arum Puspitaning Ati; Ernawaty Ernawaty (The Indonesian Journal of Public Health, 2021)
This study used the observational quantitative method to analyze the acceptance of information technology  in the form of thee-Health. The theory of acceptance was further analyzed using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. UTAUT model is the latest unified model that is an appropriate to explain the acceptance and use of information systems. The research objective was to analyze perceptions of the use of e-Health applications in the Surabaya City Health Center. The research design method used was cross-sectional design. The selected samples of 100 people were determined by multistage sampling in primary healthcare centers in every area of Surabaya. The independent variables in this study were performance expectancy, effort expectancy, social influence and behavioral intention while the dependent variable was the use of e-Health applications. Data were collected through questionnaires delivered via interviews. The results showed that the lowest indicator of acceptance by the users  was the time needed to input data category to the e-Health application. This study concludes that the acceptance of e-Health by users primary healthcare centers in Surabaya is low. This study suggests a more widespread dissemination of information regarding the benefits of the use of e-Health along with technical assistance and guidance on the use of e-Health applications.Keywords: UTAUT Model, e-Health application, primary healthcare center, acceptance